LC–MS/MS approach for simultaneous assessment of hyoscine N‐butyl bromide and ketoprofen in biological fluids and pharmaceuticals. (7th March 2023) - Ali, Hazim M.; Alsohaimi, Ibrahim Hotan; Hasanin, Tamer H. A.; Batubara, Afnan S.; Bukhary, Deena M.; Mostafa, Ehab M.; Gamal, Mohammed
Abstract: The mixture of hyoscine N ‐butyl bromide (HBB) and ketoprofen (KTP) is commonly used for the handling of abdominal spasms and pain relief. There are two challenges that restrict the simultaneous assessment of HBB and KTP in biological fluids and pharmaceuticals. The first issue is the difficulty of elution of HBB and the second one is the presence of KTP as a racemic mixture in all pharmaceutical formulations, which obscures its appearance as a single peak. An ultrasensitive and highly efficient liquid chromatography–mass/mass spectrometric (LC–MS/MS) method is designed and validated for the first concurrent assessment of HBB and KTP in spiked human serum and urine, and pharmaceutical formulations. The estimated linearity ranges for HBB and KTP were respectively, 0.5–500 and 0.05–500 ng/ml, with excellent correlation coefficients. Validation results showed that the value of relative standard deviations were <2% for HBB and KTP. The mean extraction recoveries for HBB and KTP were, respectively, 91.04 and 97.83% in Spasmofen® ampoules; 95.89 and 97.00% in spiked serum; and 97.31 and 95.63% in spiked urine. The presented innovative chromatographic approach was utilized for the measurement of trace amounts of coexisting pharmaceuticals in pharmacokinetics studies and routine therapeutic medication monitoring.